Diplomasi Vaksin Republik Rakyat Tiongkok di Asia Tenggara - Ageng, Mutiara; Albayumi, Fuat; Iqbal, Muhammad (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
At the end of 2019, the emergence of a virus outbreak that in a short time became a pandemic has become a threat to the world, this outbreak has forced many aspects of life and the world's systematics to change as well. This virus is named Coronavirus Disease-19 which is abbreviated as COVID-19. Meanwhile, after the emergence of the COVID-19 pandemic, China faced 'xenophobia' and racism from many parties regarding the first case of COVID-19 appearing in Wuhan City, Hubei Province in China, with no exception even from Southeast Asian nations. This paper will discuss the goals of the People's Republic of China in carrying out Vaccine Diplomacy in the Southeast Asian Region. With the decline of China's image, xenophobia and racism have emerged, and China has taken the initiative to carry out diplomacy to improve its image. In the current era of the COVID-19 pandemic, a new term has developed called Vaccine Diplomacy which in the implementation of Diplomacy of a vaccine country is used as a medium for its approach.